Application of Problem-based Learning Models Assisted By Liveworksheets Towards Students’ Mathematical Creative Thinking Ability - Sari, Intan Puspita; Jusra, Hella (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The ability to think creatively mathematically of students is relatively low.The purpose of this research is to determine whether employing the Liveworksheets-assisted Problem Based Learning technique influences students’ mathematics ability to think creatively. This study used quantitative research methods and a non-equivalent post-test only control group design. The sampling technique employs non-probability sampling. The sample for this study consisted of two classes with 71 students.The normality and homogeneity tests are used in quantitative research as part of the preconditioning test. In this study, the hypothesis was tested using an independent sample test. This study’s findings illustrate students’ mathematics creative thinkingÂ abilityÂ in experimental classrooms influenced by the usage of the Problem Based Learning modelÂ usingÂ liveworksheets. This demonstrates that the experimental class’s students have a greater potential for mathematical creative thinking ability than the control class.The application of problem based learning models assisted by liveworksheets influences the studentâ€™s mathematical creative thinking ability.